P13: Features of proteasome system functioning in the tumor and microenvironment cells of breast cancer. Issue 1 (November 2015) - Shashova, E.; Kolegova, E.; Lyupina, Yu.; Slonimskaya, E.; Kondakova, I.; Sharova, N.
Abstract : Background: The tumor microenvironment plays an important role in the progression of cancer and may be regulated by proteolysis, including the proteasomes. The proteasomes modify the biologically important molecules involved in the pathogenesis and progression of a variety of malignancies, including breast cancer (BC). The aim of this study was to investigate the features of the subunit composition of proteasomes in the tumor and its microenvironment of breast cancer. Material and Methods: The material for investigation was samples of tumor tissue of invasive ductal breast cancer. The study was conducted to estimate the distribution of the total pool of proteasome, proteasomes activator PA700, immune proteasome forms containing LMP7 and/or LMP2 subunit in tumor cells and stromal component using immunofluorescence. Furthermore, there was evaluated the distribution of the proteasome in the tumor. The expression of immune proteasomes and proteasomes activators in the cells was studied by immunofluorescence labeling of the cells by antibodies to immune proteasome subunits and cell markers. Fluorescence was analyzed by using a fluorescence microscope DM RXA2 ("Leica", Germany) and confocal microscope TCS SP ("Leica", Germany). The specificity of the primary antibodies was confirmed by check samples, at which the reaction was carried out only with the second antibody. No cross reaction between the first and second antibodies was tested by incubation of each primary antibodies with the opposing second antibodies. In addition, there was carried out labeling the cell nuclei by reagent Hoechst 33, 342. Results: It was found that the tumor cells comprise immune proteasomes, also PA700 and PA28 α b activators. Activator PA28 α b and immune proteasomes are localized in the cytoplasm of tumor cells, whereas α 1, 2, 3, 5, 6, 7 subunits and PA700 activator detected in the cytoplasm and in the nuclei of tumor cells. Availability of α 1, 2, 3, 5, 6, 7 subunits in the nuclei of tumor cells shows the expression of constitutive proteasome subunits. Stromal cells are characterized by a high ratio of the α 1, 2, 3, 5, 6, 7 subunits to the immune LMP2 subunit as compared to cells of invasive ductal carcinoma. This means that the pool of proteasome in tumor cells of invasive ductal cancer is enriched by the immune proteasomes as compared to stromal cells. Thus, samples of invasive ductal breast cancer contain predominantly tumor cells enriched by immune proteasomes, activators PA700 and PA28 α b. The presence of proteasomes in stromal component indicates that the tumor microenvironment also has active processes of proteolysis, with involving proteasome system. Probably the processes occurring in the stromal component contribute to the output of the proteasome into the extracellular space, which is confirmed by other researchers about the existence of circulating proteasome pools and their further participation in dissemination of cancer. This work was supported by the Russian Foundation for Basic Research (Grant numbers 13-04-00169 ).